Full inclusive education: idealistic or realistic Macedonian educational agenda - Dimitrova Radojichikj, Daniela (University of Belgrade, Faculty of special education and rehabilitation, 2021)
Introduction: According to the Macedonian educational legislation, from the school year 2022/23, all children with disabilities must be included in regular schools. Aim: The purpose of this paper is to explore the attitudes of teachers towards inclusive education of all students with disabilities, and also the factors they consider most important for the proper implementation of inclusive practices in regular schools. Method: The questionnaire “Teachers’ beliefs and attitudes towards Inclusive Education” was used to examine educators’ attitudes and beliefs about full inclusion of students with disabilities. The sample for this study consisted of a total of 346 Macedonian regular school teachers. The Statistical Package for Social Sciences Software was used to analyze the data, organize the results, and provide descriptive statistics. Results: Teachers’ attitudes towards inclusive education for all students with disabilities were divided (45.4% of them agree/strongly agree, against 41.3% who disagree/strongly disagree with this issue). The findings show that regular teachers are not sure about the level of confidence in teaching students with disabilities (M=3.15+1.10). According to teachers, the biggest barriers of inclusive education are large number of students in classrooms (68.8%), unqualified educational staff (63.6%), and the curriculum (62.1%). Conclusion: Generally, the teachers in this study accept the inclusion of children with some types of disabilities in the regular classrooms, indicating at the same time the benefits of inclusion for them and for typically developing children.
Keywords: teachers’ attitudes, pupils with disability, regular school, full inclusive education